2020
DOI: 10.1111/bcpt.13396
|View full text |Cite
|
Sign up to set email alerts
|

Use of stimulants, over‐the‐counter and prescription drugs among Danish pregnant women

Abstract: Using self‐reports and blood samples from 225 unselected Danish first trimester pregnant women, the purpose of this study was to assess their use of stimulants, for example caffeine and nicotine as well as over‐the‐counter (OTC) and prescription drugs. According to self‐reported information, 24% had used prescription drugs and 48% had used OTC drugs mainly acetaminophen (42%), 9.3% were habitual smokers, 44% stated a daily use of caffeinated beverages, and 1.3% used illegal drugs. Ultra‐performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…The wide range of reported prevalence estimates also may reflect differences in practices and healthcare systems. 19 Like other studies, 3,9,12,20 acetaminophen was the most commonly used prenatal OTC medication-72.2% of women in our study-followed aspirin and ibuprofen.…”
Section: Discussionsupporting
confidence: 74%
“…The wide range of reported prevalence estimates also may reflect differences in practices and healthcare systems. 19 Like other studies, 3,9,12,20 acetaminophen was the most commonly used prenatal OTC medication-72.2% of women in our study-followed aspirin and ibuprofen.…”
Section: Discussionsupporting
confidence: 74%
“…However, the self-reported prevalence of medication intake was limited among the women in this study as only reported by two women with normal weight and two women with obesity (equal to 5.3% of all the included women). A similar prevalence of exposure was found in blood samples from another cohort of first trimester pregnant Danish women, where traces of prescription drugs and over-the-counter medication were found in 5.3% and 8.9% of the women, respectively 40 , supporting that the self-reports reflect the actual exposure pattern. Overall, it is a strength of the present study, that the amount of pharmacological exposures are indeed very limited, hereby providing stronger data on the impact of maternal body composition on ABCB1 and ABCG2 expression.…”
Section: Discussionsupporting
confidence: 72%
“…In studies on self‐reported usages of OTC medications, up to more than half of first‐trimester pregnant women use acetaminophen 32,33 . However, cross‐sectional studies reveal only acetaminophen in 7.1–8.9% of blood samples of first‐trimester pregnant women, indicating that the self‐reported use was only occasionally 34,35 . OTC medication effects should be included when considering foetal harmful effects of polypharmacy in early pregnancy 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…32,33 However, cross-sectional studies reveal only acetaminophen in 7.1-8.9% of blood samples of firsttrimester pregnant women, indicating that the selfreported use was only occasionally. 34,35 OTC medication effects should be included when considering foetal harmful effects of polypharmacy in early pregnancy. [36][37][38] All studies try to take some confounding factors into account by matching, exclusion or adjusting; however, only few studies 24,25 adjust for the most common factors for congenital malformations like maternal age, 39 smoking 40 or BMI.…”
Section: Summary and Interpretation Of Evidence Levelmentioning
confidence: 99%